Assessment and the logic of instructional practice in Secondary 3 English and mathematics classrooms in Singapore. Issue 1 (25th February 2013) - Hogan, David; Chan, Melvin; Rahim, Ridzuan; Kwek, Dennis; Maung Aye, Khin; Loo, Siok Chen; Sheng, Yee Zher; Luo, Wenshu
<x xml:space="preserve">Abstract</x> By any measure, Singapore's educational system has generated an extraordinary record of achievement over the past two or three decades. In this article, we report on one key component of a broader three year investigation into why Singapore has done so well, and explore the logic, strength, resilience and limits of the underlying pedagogical model and policy framework that have helped secure this record of achievement. Specifically, we draw on data we collected in 2010 to analyze the pedagogical organization of four theoretically specified 'models' of instructional strategy–traditional instruction, direct instruction, teaching for understanding, and co‐regulated learning strategies–in Secondary 3 mathematics and English. In the course of our analysis, we develop three arguments. The first is the single‐minded performative orientation of instructional practices generally–and instructional strategies specifically–in Singaporean classrooms that rarely deviated from a logic of curriculum coverage, knowledge transmission and assessment. Second, while we found substantial evidence of a pervasive performative orientation to instruction, we also found that teachers in Singapore draw from a variety of instructional perspectives in ways that reflect a pragmatic, instrumental fit‐for‐purpose approach and broader performative orientation. Third, we found that the national high stakes assessment system, by virtue of its considerable institutional authority, both shaped the pattern of instructional practice at the classroom level and constrained opportunities for instructional improvement. In the conclusion, we review related findings from the research program on the impact of instructional practice on student achievement in Singapore.